2010
DOI: 10.1016/j.rbmo.2010.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for frozen–thawed embryo transfer cycles: a double-blind randomized controlled trial

Abstract: The role of acupuncture on the pregnancy rate has not been evaluated in frozen-thawed embryo transfer (FET) cycles. This randomized double-blind study aimed to determine whether acupuncture performed on the day of FET improves clinical outcomes. On the day of FET, 226 patients were randomly allocated to either real or placebo acupuncture according to a computer-generated randomization list in sealed opaque envelopes. They received a session of real or placebo acupuncture for 25 min on site immediately after FE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(105 citation statements)
references
References 33 publications
(47 reference statements)
3
97
2
1
Order By: Relevance
“…In all, 4 trials [28,33,34,35] were included when acupuncture was performed after and around the time of ET (1 in Germany [33], 1 in Denmark [28] and 2 in China [34,35]). The characteristics of the included trials are summarized in table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, 4 trials [28,33,34,35] were included when acupuncture was performed after and around the time of ET (1 in Germany [33], 1 in Denmark [28] and 2 in China [34,35]). The characteristics of the included trials are summarized in table 2.…”
Section: Resultsmentioning
confidence: 99%
“…In this case we put the ACU1 patients into the group of acupuncture around ET and the ACU2 subjects into the group of acupuncture after and around ET. The studies of So et al [35] and Zhang et al [34] used electroacupuncture in the trials, whereas the others used traditional needle acupuncture.…”
Section: Resultsmentioning
confidence: 99%
“…Andersen et al administrated real or placebo acupuncture on the day of ET in 635 patients and found no difference of pregnancy rates in the two groups and implied that the effect of acupuncture in pregnancy rates was only a placebo effect [34]. So et al conducted a randomized double-blinded comparison between real and placebo acupuncture on IVF outcomes, in this trial, both groups received the acupuncture in pre-transplant of the embryo, and found that the placebo group achieved significantly higher pregnancy rates than real group (55.1% versus 43.8%; P < 0.038); furthermore, there were no differences in ongoing pregnancy rates and live birth rates in the two groups [35], and the same results were obtained in these patients undergoing frozen-thawed embryo transfer (FET) cycles [36]. Madaschi et al also did not find increased pregnancy rates in patients who received acupuncture before and after ET and indicated that the use of acupuncture in patients undergoing IVF was not associated with an increase in pregnancy rates [37].…”
Section: The Utilization Of Acupuncture and Moxibustion In Subfertmentioning
confidence: 93%
“…Diese randomisierte kontrollierte Studie (RCT) zeigte eine signifikante Verbesserung der Schwangerschaftsrate (SR) bei Patientinnen mit Akupunkturbehandlungen kurz vor und nach dem Embryotransfer (ET) [12]. In einigen der darauffolgenden RCTs konnte der günstige Einfluss von Akupunktur auf die SR bestätigt werden [14,15], während in anderen keine signifikanten Unterschiede zwischen der Akupunktur-und der Kontrollgruppe [16][17][18][19][20][21][22], und zum Teil eine signifikant höhere SR in der Kontrollgruppe [23,24] …”
Section: Modalities Of Acupuncture Treatments In Assisted Reproductivunclassified